Pengaruh konflik peran ganda (work family conflict) terhadap keberhasilan usaha (studi kasus pada Ikatan Pengusaha Muslimah Indonesia di Kota Jambi) - Kiki Widyasari; Dahmiri Dahmiri; Sigit Indrawijaya (Prodi Magister Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2019)
This study aims to analyze the effect of multiple role conflicts on the business's success in the Jambi City IPEMI. This research was held at the IPEMI Gallery located on the Kambang River in Jambi City. The population in this study were Muslim women entrepreneurs who were members of the Jambi City IPEMI as many as 613 people. The sample in this study was 86 respondents using the probability sampling method, namely simple random sampling. The dependent variable in this study is multiple role conflict, and the independent variable is business success. This study shows that partially influencing considerable role conflict positively and significantly affects business success.